Framing the Industry: Front-Page Coverage of Intercollegiate Athletics in Five Major Newspapers - Erianne A. Weight; Coyte G. Cooper (Journal of Applied Sports Management, 2015)
This study examined the prevalence, content, and tone of front page intercollegiate athletic coverage within daily sampling of five major newspapers during the 2011 calendar year through a theoretical lens of framing as a theory of media effects. Analysis reveals broad media presentation of an industry characterized by lavish spending and widespread corruption in football and men's basketball with roughly 98% of the college sport-coverage word count devoted to men's sport with 73.7% covering football and 23.8% covering men's basketball with dominant emergent themes including financial exorbitance, scandal, athlete compensation, conference realignment, conflict between athletics & the academy, athlete entitlement, athlete discipline problems, coach power, and hyper-competitiveness.
Keywords: Intercollegiate athletics; college sport; framing; media effects; reform; publicity; public discourse; newspaper coverage